2012
DOI: 10.1371/journal.pone.0047365
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cells and Microparticles as Prognostic Markers in Advanced Non-Small Cell Lung Cancer

Abstract: BackgroundCirculating endothelial cells and microparticles have prognostic value in cancer, and might be predictors of response to chemotherapy and antiangiogenic treatments. We have investigated the prognostic value of circulating endothelial cells and microparticles in patients treated for advanced non-small cell lung cancer.Methodology/Principal FindingsPeripheral blood samples were obtained from 60 patients before first line, platinum-based chemotherapy +/− bevacizumab, and after the third cycle of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 37 publications
7
57
2
Order By: Relevance
“…After a multivariate regression analysis, these higher levels were an independent predictor of 1-year mortality. This result was clearly in contrast with the study by FLEITAS et al [59]. Moreover, in a previous study on the topic by the same investigators [61], both PMP and EMP levels were higher in 130 lung cancer patients compared with 30 healthy controls, but they were not associated with the presence of metastasis or with cancer stage (early versus advanced).…”
Section: Lung Cancercontrasting
confidence: 74%
See 1 more Smart Citation
“…After a multivariate regression analysis, these higher levels were an independent predictor of 1-year mortality. This result was clearly in contrast with the study by FLEITAS et al [59]. Moreover, in a previous study on the topic by the same investigators [61], both PMP and EMP levels were higher in 130 lung cancer patients compared with 30 healthy controls, but they were not associated with the presence of metastasis or with cancer stage (early versus advanced).…”
Section: Lung Cancercontrasting
confidence: 74%
“…These have mostly focused on the possible prognostic value of microparticles in lung cancer but the results were discordant. FLEITAS et al [59] found higher levels of total circulating microparticles in 60 patients with nonsmall cell lung cancer compared with 60 controls, but the most relevant finding was that, in cancer patients, higher baseline levels of microparticles were associated with a better progression-free and overall survival. Discordant results emerged from another study conducted in 107 end-stage nonsmall cell lung cancer patients, divided into 1-year survivors and nonsurvivors, measuring PMPs and EMPs [60].…”
Section: Lung Cancermentioning
confidence: 98%
“…Finally, there is a Spanish work which also analyzes the role of CEC in NSCLC: Fleitas et al [23] determined the number of CEC in 60 patients with NSCLC by inmunomagnetic separation. No statistically significant association between baseline CEC levels and response was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The results show significant differences as both predictive and prognostic factor in terms of response and survival [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported the presence of MPs in the plasma of cancer patients (Fleitas et al 2012;Savasan et al 2004;Toth et al 2008). Liebhardt et al (2010) analyzed the MPs in the plasma of breast cancer patients and identified four major subpopulations of MPs including a group positive for BCRP (BCRP + ).…”
Section: Microparticles and Cancer Resistancementioning
confidence: 97%